Quantum Dots-Based Immunochromatographic Strip for Rapid and Sensitive Detection of Acetamiprid in Agricultural Products - Liu, Ying (Front Chem, 2019)
In this study, a rapid and sensitive immunochromatographic strip (ICS) assay, based on quantum dots (QDs), was developed for the qualitative and quantitative detection of acetamiprid in agricultural samples. Acetamiprid-ovalbumin conjugates (ACE-OVA) and goat anti-mouse IgG were sprayed onto a nitrocellulose membrane as a test and control line. Two kinds of anti-acetamiprid monoclonal antibodies (mAb) obtained in our lab were characterized by the ELISA and surface plasmon resonance assay. The competitive immunoassay was established using a QDs-mAb conjugate probe. The visual detection limit of acetamiprid for a qualitative threshold was set as 1 ng/mL to the naked eye. In the quantitative test, the fluorescence intensity was measured by a portable strip reader and a standard curve was obtained with a linear range from 0.098 to 25 ng/mL, and the half maximal inhibitory concentration of 1.12 ng/mL. The developed method showed no evident cross-reactivities with other neonicotinoid insecticides except for thiacloprid (36.68%). The accuracy and precision of the developed QDs-ICS were further evaluated. Results showed that the average recoveries ranged from 78.38 to 126.97% in agricultural samples. Moreover, to test blind tea samples, the QDs-ICS showed comparable reliability and a high correlation with ultra-performance liquid chromatography-tandem mass spectrometry. The whole sample detection could be accomplished within 1 h. In brief, our data clearly manifested that QDs-ICS was quite qualified for the rapid and sensitive screening of acetamiprid residues in an agricultural product analysis and paves the way to point-of-care testing for other analytes.